THE CONCEPT OF VALUE MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article considers and explores organizational values, which are defined as values that are perceived by all employees of the enterprise, understood by them, and therefore their cooperation is coordinated to achieve a specific goal of the business structure, from which each team member benefits. The result of doing business on common values is effective cooperation, and common values and goals create trust.Results. It is substantiated that value management is a concept that combines ethical, social and economic paradigm in the modern business structure, as issues of ethics and social responsibility are perceived by modern enterprises as a source of competitive advantage, recognizing the direction of increasing their market value. The defining role of values stems from their key impact on behavior in the business structure and the establishment of directions of its activities, because they are the main connecting factor of all components of the enterprise.The genesis and differences of the concept of value management from ethics in management are analyzed the Corporate Social Responsibility (CSR), the Value Based Management (VBM).Four trends in business that contributed to the creation of MBV are considered. The first trend is related to product quality and consumer orientation. The second trend is related to technical progress, which requires the involvement of professionals. Rules, instructions and goals cannot be followed to gain the support of such employees. The third trend is about leaders and the quality needed to inspire and spread the efforts of professional organizations. The fourth trend is generated by the complexity and speed of changes in the environment. To survive, the enterprise must be well structured and flexible.In order to improve the concept of MBV, its shortcomings are considered: ambiguity of the concepts of "value", differentiation of employees in terms of their potential systemic problems, polarization of enterprises in terms of value, interference in professional and private life of staff.Conclusions. It is noted the integration and internationalization of corporate and personal values of the enterprise are areas of change in management theory, which will make their management more mature.
Keywords: value management, organizational values, trend, management ethics, social responsibility concepts (SRC), Value Based Management (VBM).